Platón en 90 minutos - Strathern, Paul, 1940-; Padilla Villate, José Antonio; Strathern, Paul, 1940- (Tres Cantos, Madrid, España : Siglo XXI de España Editores, S.A., 2014)
Paul Strathern offers a concise account of Plato's life and ideas, and explains their influence on man's struggle to understand his existence in the world. The book also include sections from Plato's work; a brief list of suggested reading for those who wish to push further; and chronologies that place Plato within his own age and in the broader scheme of philosophy.
Online resource; title from ePub title page (Digitalia, viewed June 28, 2017)
Keywords: Plato; Philosophers, Ancient -- Biography; Philosophy, Ancient; Electronic books